Nutritional values of minor carps (SAARC Journal of Agriculture, 2018)
The nutrient profile of five carps, viz. Labeo bata, Labeo calbasu, Labeo fimbriatus, Cirrhinus reba and Puntius javanicus were studied. The samples were collected from different geographical locations of West Bengal, Odisha and Karnataka states of India. The data on proximate composition reveal that the moisture and fat content differed significantly (P